What is known about the LGBTQ perspective in child welfare services: A scoping review. Issue 2 (14th December 2021) - Kaasbøll, Jannike; Pedersen, Sindre Andre; Paulsen, Veronika
Abstract: Sexual and gender minorities, for example, lesbian, gay, bisexual, transgender and questioning (LGBTQ) youth, are overrepresented in the child welfare system and an increasing number of LGBTQ people are becoming foster parents. The objective of this scoping review is to provide an overview of the existing empirical research on the practices of child welfare services towards LGBTQ individuals (i.e., youth, carers and foster parents). The review followed the methodology framework outlined by the Joanna Briggs Institute (JBI). The electronic databases MEDLINE, Embase, PsycINFO, Web of Science, PubMed and Idunn were searched to identify studies appropriate for inclusion. There were 45 studies that met the inclusion criteria; 24 concerned LGBTQ youth, 10 encompassed foster parents, while nine had the service perspective as the primary focus. The studies originated from the USA ( k  = 34), the UK ( k  = 6), Australia ( k  = 2) and the Netherlands ( k  = 1). Of the included studies, 28 were qualitative, 14 were quantitative, and three studies used mixed method approach. The findings indicate that LGBTQ youth are overrepresented in the child welfare system and that LGBTQ youth and foster parents often face stigma and discrimination. The results reveal a gap in the current knowledge about social workers' attitudes, knowledge and experiences regarding working with LGBTQ individuals.